Implementation of Green Business Model in Culinary SMEs in Lampung for Sustainable Development - Putri Irmala Sari; Supri Yanto; Nelly Suryani (Journal of Innovative and Creativity, 2026)
The study aims to analyze the implementation of the Green Business Model (GBM), identify the key influencing factors, measure its economic and environmental impact, and understand the associated challenges. Methodologically, it employs a quantitative approach, conducting a survey of 384 culinary SMEs selected through stratified random sampling. The collected data were analyzed using Structural Equation Modeling (SEM) with AMOS 24.0 software to test the hypothesized relationships between variables.The key findings reveal that the implementation level of GBM is currently medium. Management commitment was identified as the most significant driver. The adoption resulted in substantial benefits: a 23.4% increase in profitability, an 18.7% reduction in operating costs, and a 31.2% decrease in organic waste. Financial performance and environmental impact were found to be effective mediators for achieving sustainable development.The main implication is the creation of a tailored GBM framework for Indonesian culinary SMEs. The study offers the theoretical contribution of "locally embedded sustainability," emphasizing the need to adapt sustainable models to local contexts, thereby enriching the literature on business model innovation in developing countries.